Seasonal Thermal Energy Storage Using Sand Batteries: Feasibility and Economic Analysis in Northern Norway - Strømsør, Audun (UiT The Arctic University of Norway, 2024)
The global shift from fossil fuels to renewable energy sources necessitates effective energy storage solutions to address the intermittent nature of renewable power. This thesis investigates the feasibility and economic viability of using sand batteries for seasonal thermal energy storage in Northern Norway. Sand batteries leverage the high heat capacity of sand to store excess thermal energy during summer for use in winter, potentially providing a sustainable solution to meet heating demands in cold climates. The research employs a computational model developed in COMSOL Multiphysics to simulate the heat transfer processes within a sand battery system. Key parameters, such as energy storage capacity, efficiency, and economic implications, are evaluated using data from the Tibber app, which monitors household energy consumption. The simulation results indicate that sand batteries can effectively store substantial amounts of energy and provide significant cost savings during the winter months by meeting heating needs. However, the analysis reveals challenges in achieving economic viability over the system's lifecycle under current conditions, primarily due to high initial costs, inefficiencies in the charging process, and variable electricity prices. Sensitivity analyses suggest that optimizing the charging and discharging cycles can significantly enhance the system's economic viability. Charging during periods of low electricity prices and discharging during high-demand periods, along with improving charging efficiency, can lead to much higher annual savings and a favourable economic outcome over the long term. These findings highlight the potential of sand batteries as a viable thermal energy storage solution, with further research needed to optimize system efficiency and economic performance. The integration of smart grid technologies and real-world pilot projects are recommended to validate the model's predictions and explore the scalability of sand battery systems in diverse geographical settings.